Interpreting sulci on hominin endocasts: old hypotheses and new findings - Falk, Dean (Frontiers in Human Neuroscience, 2014)
Paleoneurologists analyze internal casts (endocasts) of fossilized braincases, which provide information about the size, shape and, to a limited degree, sulcal patterns reproduced from impressions left by the surface of the brain. When interpreted in light of comparative data from the brains of living apes and humans, sulcal patterns reproduced on hominin endocasts provide important information for studying the evolution of the cerebral cortex and cognition in human ancestors. Here, new evidence is discussed for the evolution of sulcal patterns associated with cortical reorganization in three parts of the hominin brain: (1) the parietotemporo-occipital association cortex, (2) Broca’s speech area, and (3) dorsolateral prefrontal association cortex. Of the three regions, the evidence regarding the last is the clearest. Compared to great apes, Australopithecus endocasts reproduce a clear middle frontal sulcus in the dorsolateral prefrontal cortex that is derived toward the human condition. This finding is consistent with data from comparative cytoarchitectural studies of ape and human brains as well as shape analyses of australopithecine endocasts. The comparative and direct evidence for all three regions suggests that hominin brain reorganization was underway by at least the time of Australopithecus africanus (~ 2.5 to 3.0 mya), despite the ape-sized brains of these hominins, and that it entailed expansion of both rostral and caudal association cortices.